Isolation and Large Scale Expansion of Human Endothelial Progenitor Cells from Peripheral Blood - Gubar, Olga S.; Rodnichenko, Anzhela E.; Zlatska, Olena V.; Zubov, Dmytro O.; Litvinova, Larisa S.; Shupletsova, Valeria V.; Vasyliev, Roman G. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 029–033